Absence of Fer protein tyrosine kinase exacerbates endotoxin induced intestinal epithelial barrier dysfunction in vivo. Issue 8 (11th July 2005) - Qi, W; Ebbert, K V J; Craig, A W B; Greer, P A; McCafferty, D-M
Abstract : Background and aims: Fer kinase is activated by a number of growth factors and cytokines, and phosphorylates cortactin during cell shape change induced cortical actin reorganisation. In addition, Fer participates in cytoskeletal interactions mediated by cadherins, platelet endothelial cell adhesion molecule 1 (PECAM-1), and integrins, and has recently been implicated in limiting the innate immune response. Here we examined the role of Fer in modulating leucocyte recruitment and epithelial barrier function in the gut in response to lipopolysaccharide (LPS). Methods: Mice targeted with a kinase inactivating mutation (FerDR) or strain matched wild-type (129Sv/J) mice were studied after intraperitoneal injection of LPS. Intravital microscopy was used to examine intestinal leucocyte kinetics, and leucocyte infiltration was assessed by fluorescence activated cell sorting. Systemic inflammation was assessed by measuring lung myeloperoxidase activity. Epithelial barrier function was assessed in vivo using blood to lumen 51 Cr-EDTA clearance, with or without antibody based depletion of circulating neutrophils. Results: LPS induced a significant increase in leucocyte adhesion and neutrophil infiltration into the intestinal tissue, and increased blood to lumen 51 Cr-EDTA clearance. Pretreatment with neutrophil depleting antibody completely abrogated this response in wild-type mice. In FerDR mice, LPS induced leucocyte adhesion within the intestinal venules was exacerbated and associated with a trend towards increased neutrophil transmigration relative to wild-type mice. Surprisingly, LPS induced epithelial barrier permeability was increased 2.5-fold in FerDR mice relative to wild-type mice, and this barrier defect was only partly attenuated by depleting circulating neutrophils by >93 %. Conclusions: Fer plays a role in regulating LPS induced epithelial barrier dysfunction in vivo through both neutrophil dependent and neutrophil independent mechanisms.